IgG subclass and Fc glycosylation shifts are linked to the transition from pre- to inflammatory autoimmune conditions - Buhre, Jana Sophia; Becker, Mareike; Ehlers, Marc (Frontiers in Immunology, 2022)
A crucial factor for the development of inflammatory autoimmune diseases is the occurrence of antibodies directed against self-tissues and structures, which leads to damage and inflammation. While little is known about the cause of the development of mis-directed, disease-specific T and B cells and resulting IgG autoantibody responses, there is increasing evidence that their induction can occur years before disease symptoms appear. However, a certain proportion of healthy individuals express specific IgG autoantibodies without disease symptoms and not all subjects who generate autoantibodies may develop disease symptoms. Thus, the development of inflammatory autoimmune diseases seems to involve two steps. Increasing evidence suggests that harmless self-directed T and B cell and resulting IgG autoantibody responses in the pre-autoimmune disease stage might switch to more inflammatory T and B cell and IgG autoantibody responses that trigger the inflammatory autoimmune disease stage. Here, we summarize findings on the transition from the pre-disease to the disease stage and vice versa, e.g. by pregnancy and treatment, with a focus on lower-/anti-inflammatory versus pro-inflammatory IgG autoantibody responses, including IgG subclass and Fc glycosylation features. Characterization of biomarkers that identify the transition from the pre-disease to the disease stage might facilitate recognition of the ideal time point of treatment initiation and the development of therapeutic strategies for re-directing inflammatory autoimmune conditions.